PERSEPSI MAHASISWA TERHADAP KODE ETIK AKUNTAN BERDASARKAN GENDER (Studi Kasus Pada Mahasiswa Akuntansi STIE Dharmaputra Semarang) - Watinih .; Putu Sulastri (LPPM STIE DHARMAPUTRA SEMARANG, 2016)
ABSTRACTION This study examined students perceptions of ethical principles, ethical rules, the interpretation of rules of ethics code of ethics accountant by gender. The research object is a student STIE Dharmaputra Semarang accounting majors who are already working and students who have taken auditing. The samples used were 84 people with purposive sampling method. To analyze the use of t-test with SPSS. The results showed that based on gender, ethical principles, ethical rules, the interpretation of the ethical rules of the code of ethics of accountants showed a significant difference. Keywords : Perception of Students, Accountants Code of Ethics, Gender.